Content and Language Integrated Learning (CLIL) to work on students’ reading comprehension skills. - Apo Muso, Irene Anabell (2023)
Receptive skills (reading and listening) are the fundamental skills on which CLIL focuses. Therefore, CLIL offers the possibility of developing critical thinking through strategies based on analysis and comprehension. Therefore, there are different strategies that allow the development of reading competence. In this sense, teachers should use strategies such as; paraphrasing, inferring, summarizing, predicting, questions, maps, and connections, among others, during the process of learning to read. In this context, the project entitled ''Content and Language Integrated Learning (CLIL) to Work on Students’ reading comprehension'' was proposed with the main objective of analyzing the effectiveness of the CLIL methodology in the development of reading comprehension skills in English. This research presents a qualitative approach and an interpretative level. Likewise, the research adopts a field and documentary approach since the data was collected in the place where the events took place. Also, information was collected from bibliographic sources. Additionally, an observation guide and interview were utilized to obtain relevant information about the study population, which consisted of 17 students and an English teacher from Primer Año de Bachillerato General Unificado ''A'' at ''Unidad Educativa Camilo Gallegos Toledo''. The results indicate that CLIL reading was significant in the development of reading comprehension. In addition, the need to design activities according to the level of study of the students was evidenced. Finally, it was determined that it is essential to apply comprehension strategies throughout the process to teach reading '' Pre, during, and post-reading'' to obtain better results.